Training-related changes in force-power profiles: Implications for the skeleton start - Colyer, S. L.; Stokes, K. A.; Bilzon, J. L. J.; Holdcroft, D.; Salo, A. I. T. (International Journal of Sports Physiology and Performance, 2018)
Athletes` force-power characteristics influence sled velocity during the skeleton start, which is a crucial determinant of performance. This study characterized force-power profile changes across an 18-month period and investigated the associations between these changes and start performance. Methods: Seven elite- and 5 talent-squad skeleton athletes` (representing 80% of registered athletes in the country) force-power profiles and dry-land push-track performances were assessed at multiple time points over two 6-month training periods and one 5-month competition season. Force-power profiles were evaluated using an incremental leg-press test (Keiser A420), and 15-m sled velocity was recorded using photocells. Results: Across the initial maximum strength development phases, increases in maximum force (Fmax) and decreases in maximum velocity (Vmax) were typically observed. These changes were greater for talent (23.6% and -12.5%, respectively) compared with elite (6.1% and -7.6%, respectively) athletes. Conversely, decreases in Fmax (elite -6.7% and talent -10.3%) and increases in Vmax (elite 8.1% and talent 7.7%) were observed across the winter period, regardless of whether athletes were competing (elite) or accumulating sliding experience (talent). When the training emphasis shifted toward higher-velocity, sprint-based exercises in the second training season, force-power profiles seemed to become more velocity oriented (higher Vmax and more negative force-velocity gradient), which was associated with greater improvements in sled velocity (r?=?.42 and -.45, respectively). Conclusions: These unique findings demonstrate the scope to influence force-power-generating capabilities in well-trained skeleton athletes across different training phases. To enhance start performance, it seems important to place particular emphasis on increasing maximum muscle-contraction velocity.